ANALISIS PENGARUH DAYA TERIMA PASAR, TARIF DAN PERSEPSI MUTU PROSES PEMBELAJARAN & PELAYANAN TERHADAP PENINGKATAN MINAT PADA JURUSAN ADMINISTRASI NIAGA POLITEKNIK NEGERI SEMARANG - Dwi Astuti, Rif’ah (STIE Totalwin Semarang, 2011)
This study analyzes the effect of receive, tariffs and quality perceptions of the learning process and service to increase interest. The formulation of the questions examined in this study were 1). What impact will influence the perception of market acceptance for graduates of interest in selecting majors AN? 2). What impact do perceptions influence the rates of interest specified AN AN chose? and 3). What impact will influence the perception of the quality of the learning process and service in the AN of interests to choose majors AN? Furthermore, variables and indicators of research is also based on previous research. A model has been developed and three hypotheses have been formulated to address this research problem. The sampling technique was purposive sampling and quota sampling. Respondents from this study amounted to 100 respondents, where respondents were students of the Department AN Semarang State Polytechnic. Data analysis tool used is Structural Equation Modelling (SEM) in AMOS 16.0. The results of this study data analysis shows the model and research results were well received, and further research is proving the influence of perception on the market acceptance of graduates AN interest in the Department of the AN is positive and significant. Effect of tariff AN Perception of interest in the Department of the AN is not significant. Then the influence of the effectiveness of advertising on consumer buying behavior is positive and significant. And the influence of the learning process and service quality in the AN of interest in the Department is positive and significant